Kenyamanan Termal Klimatologis di Provinsi Riau berdasarkan Temperature Humidity Index (THI) - Tia Kustia; Tomy Burju Asido Sihombing (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2022)
Enhancement of population and migration that trigger development and industrial growth if it is not balanced by environmental balancing and land availability will cause environmental and social problems as well as reduced green open space which will affect human comfort in their activities. This research aims to determine the level of thermal comfort and its tendency in Riau Province using the THI index. This study uses the variables of daily average air temperature and daily relative humidity for the period 1990 – 2021 from Meteorological Station SSK II Riau to calculate the THI index. Based on the results of the calculation of the THI index, in general the level of comfort in the Partially Comfortable category is 84.3% or 308 days/year and the trend of THI has increased by 0.019 C/year.